Addition of an adipose marker to the organ tissue identification mRNA assay. (December 2022) - van den Berge, Margreet; Sijen, Titia
Abstract: At the Netherlands Forensic Institute, mRNA profiling for the purpose of organ tissue identification is frequently requested in casework. The previous version of the assay (denoted Organtyper) lacked markers for identifying adipose tissue, while this was occasionally questioned in casework. Here, three potential adipose markers are examined before incorporating one into the final Organtyper assay. The added value of the adipose marker becomes clear from looking at casework results.